Management Training and Supervisory Leadership in Improving Performance for Regional Structural Officials - Nanang Chaeroni; Sutaryat Trisnamansyah; Ikka Kartika AF; Yosal Iriantara (Yayasan Azka Hafidz Maulana, 2023)
The background of this research is that the quality of graduates of Supervisory Leadership Training (SLT) Batch 3 at the GRSDM of the Ministry of Home Affairs of the Republic of Indonesia in Bandung Region is still low, especially those who occupy Esselon officials. The low quality of graduates is strongly influenced by various interrelated components, including; input of training participants, teaching and learning process, human resources, infrastructure, operational and environmental budgets. In order for the outputs and outcomes of the training participants to be better, there must be a commitment from the education and training leadership and all stakeholders to improving the quality of education and training graduates through integrated program Planning, implementation and evaluation. The purpose of this study was to determine the activities carried out in Planning, organizing, evaluating in GRSDM Education and Training, obstacles encountered and solutions to overcome the obstacles. This study uses a qualitative Approach based on the results of observations, interviews and documentation. This study uses the main theory, namely the management theory of Terry. The results of the study show: 1) In Planning is made to avoid failure or chaos in the implementation of SLT activities, then the Planning is made in detail. 2) In the SLT organization fosters and guides in providing instructions, directions in ways to analyze and solve problems in each assignment given by GRSDM; 3) InThe implementation of SLT will motivate participants to do something if they feel confident that they will be able to, believe that the work will benefit them; 4) InLearning assessment carried out to training participants is a stage to measure abilities as input in making specific decisions 5) The obstacles encountered areImproving the quality of action for change and public service innovation in its implementation does not always run smoothly because there are many challenges and obstacles that will be faced; 6) The solution, to solve the problem is actualization of the basic values ​​of quality commitment in carrying out the duties of the apparatus as a solution that can encourage the creation of a superior work climate or culture that can foster courage to display creativity and innovation for change action.